Gairaigo in Japanese and Its Cultural Implication - Afif Kharisma Erlina; Oktavianus Oktavianus; Lindawati Lindawati (Masyarakat Linguistik Indonesia Universitas Andalas, 2022)
This research is an attempt to study gairaigo in Japanese. The study is focused on the formation, meaning, and cultural implication of gairaigo. The data for this study are Japanese loan words borrowed from English taken from NHK Easy Japanese News from May 2021 to October 2021. The research used qualitative and quantitative approaches.Â The data are collected by using the non-participant observation method.Â The analysis of data is done by using the intralingual equivalent method. The result of the study shows from 32 gairaigo collected from NHK Easy Japanese News, 98% of them are adapted to the Japanese linguistic system in the form of sound insertion and substitution. The formation of gairaigo is done by adjusting linguistic forms of English into Japanese. The formation of gairaigo causes the change in meaning which also implies Japanese culture.Â The formation of gairaigo while maintaining the linguistic features of the Japanese language is a sign of the language loyalty of Japanese speakers to their language.